Reducción de costos aplicando herramientas de calidad en la línea de producción de la planta de agregados S.R.L - Noriega Briones, Dennis Enrique (2019)
ABSTRACT This research work is focused on reducing production costs, establishing hierarchical lines of quality control through the basic tools. For this, it is possible to identify the strategic, tactical and operational objectives that lead us to look for solution indicators. The aggregates S.A.C plant, when faced with increasingly strong competitive pressures, has the need to coordinate the activities of its functions in a coherent strategy that integrates each and every one of its functions perspectives. After an initial evaluation, it was observed that the plant does have the ISO 19001 certification which has not had a continuous sustainability during the processes, therefore the products were not compliant, which led to using other methods looking for alternatives to improve the products applying quality tools, so it focused as the first objective in analyzing the raw material and final product, thus minimizing the costs of direct labor, machine hours, man hours, inputs, among others. Finally, the following was obtained: lowering 1% of the fineness module to the coarse crushed aggregate, 3% of the fine aggregate and finally the raw material to 95% purity, the costs varied from S /. 364,746 to S /. 182,129. The statistical analysis of the entire development corresponded to a “t” student test for peer comparison of the combined productivity and quality indices at 95% reliability, confirming the effect of the planned study.